Correction to: Understanding the genetic complexity of puberty timing across the allele frequency spectrum (Nature Genetics, (2024), 56, 7, (1397-1411), 10.1038/s41588-024-01798-4) - Kentistou, Katherine A.; Kaisinger, Lena R.; Stankovic, Stasa; Vaudel, Marc; Mendes de Oliveira, Edson; Messina, Andrea; Walters, Robin G.; Liu, Xiaoxi; Busch, Alexander S.; Helgason, Hannes; Thompson, Deborah J.; Santoni, Federico; et al. (Nature Genetics, 2024)
Correction to: Nature Geneticshttps://doi.org/10.1038/s41588-024-01798-4, published online 1 July 2024. In the version of the article initially published, in Fig. 5c, the trajectory labels now reading T01, T02, T03, T04, T05, T06, T07, T08, T09 and T10 appeared incorrectly as T-01, T-02, T-03, T-04, T-05, T-06, T-07, T-08, T-09 and T-10. The figure has now been amended in the HTML and PDF versions of the article.
CRIS-Team Scopus Importer:2024-11-01